2015
DOI: 10.1002/jeab.141
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary conditional discriminative functions of meaningful stimuli and enhanced equivalence class formation

Abstract: Equivalence class formation by college students was influenced through the prior acquisition of conditional discriminative functions by one of the abstract stimuli (C) in the to-be-formed classes. Participants in the GR-0, GR-1, and GR-5 groups attempted to form classes under the simultaneous protocol, after mastering 0, 1, or 5 conditional relations between C and other abstract stimuli (V, W, X, Y, Z) that were not included in the to-be-formed classes (ABCDE). Participants in the GR-many group attempted to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…Replication of Prior Experiments Prior experiments have shown a very high concordance between the formation of equivalence classes measured using MTS-formatted derivedrelations tests and the maintenance of those classes measured with post-class-formation sorting tests Fields et al 2014;Nartey et al 2014;Nedelcu et al 2015;Travis et al 2014). When classes were formed, post-class formation sorting tests showed class maintenance; when classes did not form, the post-class-formation sorting tests also showed the absence of experimenter defined categorization of the stimuli.…”
Section: Discussionmentioning
confidence: 87%
“…Replication of Prior Experiments Prior experiments have shown a very high concordance between the formation of equivalence classes measured using MTS-formatted derivedrelations tests and the maintenance of those classes measured with post-class-formation sorting tests Fields et al 2014;Nartey et al 2014;Nedelcu et al 2015;Travis et al 2014). When classes were formed, post-class formation sorting tests showed class maintenance; when classes did not form, the post-class-formation sorting tests also showed the absence of experimenter defined categorization of the stimuli.…”
Section: Discussionmentioning
confidence: 87%
“…A meaningful stimulus serves many acquired stimulus control functions (Arntzen et al, ; Fields et al, ; Nedelcu et al, ; Travis et al, ). An abstract stimulus that has acquired any one of these functions will enhance the formation of an equivalence class that includes such a stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Class formation was enhanced if the abstract stimulus had first acquired a simple successive discriminative function (Arntzen et al, ), a simple simultaneous discriminative function (Arntzen et al, ), the combination of simple and successive discriminative functions (Arntzen et al, ; Fields, Arntzen, Nartey, & Eilifsen, ), an identity conditional discriminative function on a simultaneous or delayed basis (Arntzen et al, ; Fields et al, ), or an arbitrary conditional discriminative function on a simultaneous or delayed basis (Arntzen, Nartey, & Fields, ; Arntzen et al, ). In addition, class enhancement occurred if the successive discriminative function was over‐trained (Travis, Fields, & Arntzen, ), and if many arbitrary conditional discriminative functions were trained instead of just one (Nedelcu, Fields, & Arntzen, ). Because these functions are probably served by a meaningful stimulus, the class‐enhancing effect of a meaningful stimulus can also be attributed to these acquired stimulus control functions.…”
mentioning
confidence: 99%
“…However, when the A, B, D, and E stimuli were the same abstract stimuli but the C stimuli, which served as nodes, were meaningful pictures, 80 % of participants formed classes. In systematic explorations, Travis, Fields, and Arntzen (2014) and Nedelcu, Fields, and Arntzen (2015) also found that the use of the meaningful stimulus as the middle node had a substantial class enhancement effect. Thus, the formation of large multinodal classes was also enhanced by the inclusion of a meaningful stimulus as the middle node.…”
mentioning
confidence: 92%